HUBUNGAN POLA DIET DAN STATUS MEROKOK DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI WILAYAH KERJA PUSKESMAS ANAK AIR KOTA PADANG - Gusti, Dalina (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
is a blood pressure above normal where there is a disturbance inbloodvessels resulting in supplying oxygen and nutrients carried by the blood obstructed tothebody tissues that need it. Data World Health Organization (WHO) 2012 stateshypertensionaccounted for 51% of deaths from stroke and 45% of deaths from coronary heartdisease.Data from Riskesdas 2015 showed that hypertension decreased from 31.7% in 2007 to25.8%in 2015. Data from Puskesmas Anak Air showed the second most prevalence ofhypertensivedisease that was 1,002 cases. The purpose of this study to determine the relationshipbetweendietary patterns and smoking status with the incidence of hypertension in the elderly intheWork Area Puskesmas Anak Air Padang Year 2017 The type of this research is analyticresearch with cross sectional design, this researchhas been done on March until Apriel 2017, thepopulation is all elderly men in the workarea of Padang Anak Air Puskesmas, Padang city, withtotal number is 91 people. Data wascollected through interviews and questionnaires given to therespondents, then the data wereanalyzed with Univariat and Bivariat.The result of thisresearch is 93 respondents have 49 respondents (82,7%) havehypertension, 46respondent (49,5%) have bad diet pattern, 41 responden (44,1%) smoker.There was a correlationbetween dietary pattern and hypertension with p = 0,000 (p≤0,005),and there was correlationbetween smoking status and hypertension with p = 0,040 (p≤0,005).In conclusion, more than halfof respondents had hypertension and less than half hadpoor diet and smokers. There is arelationship pattern diet and smoking status with theincidence of hypertension. For that itneeds to do counseling and health education to theelderly about a good diet for people withhypertension and the danger of smoking for healthwhich will be very useful for elderly who sufferfrom hypertension and also who do notsuffer from hypertensionKeyword : hiprtension, diit pattern, smoking